Genome‐wide analysis and transcriptional regulation of the typical and atypical thioredoxins in Arabidopsis thaliana. Issue 21 (10th October 2021) - Chibani, Kamel; Pucker, Boas; Dietz, Karl‐Josef; Cavanagh, Amanda
Abstract : Thioredoxins (TRXs), a large subclass of ubiquitous oxidoreductases, are involved in thiol redox regulation. Here, we performed a comprehensive analysis of TRXs in the Arabidopsis thaliana genome, revealing 41 genes encoding 18 typical and 23 atypical TRXs, and 6 genes encoding thioredoxin reductases (TRs). The high number of atypical TRXs indicates special functions in plants that mostly await elucidation. We identified an atypical class of thioredoxins called TRX‐c in the genomes of photosynthetic eukaryotes. Localized to the chloroplast, TRX‐c displays atypical CPLC, CHLC and CNLC motifs in the active sites. In silico analysis of the transcriptional regulations of TRXs revealed high expression of TRX‐c in leaves and strong regulation under cold, osmotic, salinity and metal ion stresses. Abstract : Our study presents a comprehensive overview of the typical and atypical thioredoxins (Trxs) present in the genome of Arabidopsis. We identified a chloroplastic class of atypical Trx‐like proteins called TRX‐c, which possess specific active sites (CPLC, CHLC and CNLC). Our in silico analyses yielded detailed information about the regulation of the typical and atypical Trxs under abiotic stresses.